Exploring the dynamic interactions between internet addiction, anxiety, and loneliness in adolescents: a longitudinal cross-lagged panel model - Wang, Yuntai; Gong, Guodong (Frontiers in Psychiatry, 2025)
PurposeThe widespread adoption of the Internet has rendered adolescent Internet Addiction (IA) a major global public health concern, frequently co-occurring with psychological issues such as anxiety and loneliness. This study investigates their dynamic interrelationships.MethodsUsing a longitudinal two-wave design, data were collected from 1,720 secondary school students in Yunnan Province, China, in October 2024 (T1) and March 2025 (T2). Measures included the Internet Addiction Test (IAT), the Generalized Anxiety Disorder Scale (GAD-7), and the UCLA Loneliness Scale (ULS). A cross-lagged panel model (CLPM) was employed to examine the causal pathways among IA, anxiety, and loneliness.ResultsIA demonstrated significant temporal stability and positively predicted subsequent increases in both anxiety and loneliness. Furthermore, loneliness significantly predicted later levels of anxiety.DiscussionThese findings extend the theoretical framework of the Compensatory Internet Use Model, providing empirical evidence for the dynamic mechanisms underlying adolescent mental health. The results underscore IA and loneliness as critical intervention targets, offering significant implications for clinical practice and educational policy aimed at Chinese adolescents.